2021
DOI: 10.3389/fphar.2021.717993
|View full text |Cite
|
Sign up to set email alerts
|

Role of Specialized Pro-Resolving Mediators in Neuropathic Pain

Abstract: Inflammation and neuroinflammation are critical mechanisms in the generation of neuropathic pain that is experienced in several chronic diseases. The aberrant inflammation that triggers this pathophysiologic process can be tracked down to an exacerbated immune response, which establishes a vicious cycle and continuously recruits inflammatory cells by inducing chronic tissue damage. Recently, impairment of the cellular and molecular machinery orchestrated by specialized pro-resolving mediators (SPMs)—i.e., endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…It is reported that 15-HEPE and 17-HDHA are precursors of lipoxin A 5 and D-series resolvins, respectively (19, ), even though we could not detect these in the present study. Lipoxins and resolvins are well-known SPM family species, and many studies have demonstrated the anti-inflammatory and analgesic properties of their pharmacological treatment (20)(21)(22)(23). The present study raises the following new questions: how are ω-3 FAs selectively subjected to LOX-mediated oxidation and why are ω-3 FA-derived metabolites transiently increased in a specified period?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that 15-HEPE and 17-HDHA are precursors of lipoxin A 5 and D-series resolvins, respectively (19, ), even though we could not detect these in the present study. Lipoxins and resolvins are well-known SPM family species, and many studies have demonstrated the anti-inflammatory and analgesic properties of their pharmacological treatment (20)(21)(22)(23). The present study raises the following new questions: how are ω-3 FAs selectively subjected to LOX-mediated oxidation and why are ω-3 FA-derived metabolites transiently increased in a specified period?…”
Section: Discussionmentioning
confidence: 99%
“…These ω-3 FA-derived anti-inflammatory lipid mediators are coined "specialized pro-resolving lipid mediators" (SPMs) (19,20). Recently, there have been increasing reports regarding the pharmacological efficacy of SPMs in the treatment of pain disorders (21)(22)(23), although the biosynthetic pathways, receptors, and in vivo presence of SPMs remain to be validated (24). Whereas previous studies have reported the pathophysiological roles of specific lipid mediators of interest, comprehensive lipidomic information on pain pathology is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, roles of SPMs in neuropathic pain were elucidated, suggesting that SPM can be promising targets to counteract neuropathic pain (Leuti et al, 2021). SPM represent the endogenous inhibitors of transient receptor potential cation channel subfamily V member 1 (TRPV1), which has been with Resolvin E1 and protectin 1.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Because of its potential to also cause harm, inflammatory responses are regulated in a very complex manner, depending in part on the initiating factors, the extent of the response that is needed (i.e., the size and location of the wound) and the ability to initiate the downregulation of the response via both removal of the inciting events and elaboration of anti-inflammatory molecules, such as resolvins and related molecules [ 24 , 25 , 26 , 27 ]. In “normal” circumstances, the inflammatory response can be acute in nature followed by a resolution.…”
Section: Introductionmentioning
confidence: 99%